LEMBAGA KEUANGAN SYARIAH DAN ARBITRASE MUAMALAT INDONESIA - Hidayanto, M. Fajar (Islamic University of Indonesia, 2003)
Islamic Financial Institution and Instruments as instution is approved get optimal provit within is activities. Through assets placement on profitable investmen in minimum risk, which inspirate its mission and operational action. However, require, this instution to put great concideration â¦